Infrared and raman spectroscopic investigations of cadmium tetracyanonickelate complexes of aminopyridines - AKYÜZ, SEVİM (Elsevier, 1988)
The infrared and Raman spectra of three new complexes of the formula CdL2Ni(CN)4 {L = 2-aminopyridine or 2-amino-4-methylpyridine} and Cd(L) (NH3)-Ni(CN)4 {L = 2-amino-3-methylpyridine} are reported. It is concluded that the ring nitrogen and not the amino nitrogen is involved in complex formation. Vibrational assignments for all the bands observed are proposed. The complexes are shown to have a structure consisting of two dimensional polymeric layers formed with Ni(CN)4 ions bridged by CdL2 {L = 2-aminopy or 2-amino-4-methylpy} or Cd(NH3)(L) {L = 2-amino-3-methylpy} cations. Several modes of coordinated aminopyridines have upward wavenumber shifts in comparison to those of the free molecules. These are thought to be due to the coupling of the internal modes of aminopyridines with the MN vibrations.